Increased availability of preferred food and decreased foraging costs from degraded grasslands lead to rodent pests in the Qinghai-Tibet Plateau - Zhang, Caijun; Kang, Yukun; Yao, Baohui; An, Kang; Pu, Qiangsheng; Wang, Zhicheng; Sun, Xiaomei; Su, Junhu (Frontiers in Ecology and Evolution, 2022)
The increased population density of rodent species during ongoing grassland degradation further deteriorates its conditions. Understanding the effects of grassland degradation on rodent feeding habits is of great value for optimizing grassland management strategies. In this study, lightly degraded (LD), moderately degraded (MD), severely degraded (SD), and reseeded grassland (RG) were selected and their plant resources and soil physical properties were investigated. In addition, the study used ITS2 barcode combined with the Illumina MiSeq sequencing method to analyze the food composition and proportion of plateau zokors in different grassland conditions. The results showed that, with grassland degradation, plant biomass decreased, but the relative proportion of forbs increased (LD: 32.05 ± 3.89%; MD: 28.97 ± 2.78%; SD: 49.16 ± 4.67% and RG: 10.93 ± 1.53%). Forbs were the main food of the plateau zokor, accounting for more than 90% of their diet, and the animal had a clear preference for Potentilla species; the soil compaction of feeding habits showed a decreasing trend in the 10–25 cm soil layer, suggesting a decreased foraging cost. Nutritional analysis showed that the stomach content of crude protein in zokors feeding on MD grassland was significantly higher than that of animals feeding on the other grassland types. Structural equation modeling showed that soil physical properties and the relative biomass of forbs had significant (P < 0.05) and extremely significant (P < 0.001) impacts on the population density of plateau zokors, with direct impact contribution rates of 0.20 and 0.63. As the severity of grassland degradation increased, although the aboveground and underground biomass of the plants decreased, the proportion of food preferred by the plateau zokor increased, and the corresponding changes in the feeding environment resulted in decreased foraging energy expenditure, thereby increasing the suitability of the degraded grassland for the plateau zokor. Compared with degraded grassland, the food diversity and evenness of zokors increased, the food niche width enlarged, and the proportion of weeds decreased in RG, which increased the difficulty of obtaining food. Reseeding in grassland management is therefore an effective way to control plateau zokors.